Learning Algorithms in JavaScript from Scratch - Traub, Eric (Packt Publishing, 2020)
Make your code and programs faster and more efficient by using algorithms About This Video Explore important algorithms and understand how they work Learn the skills and concepts that you need to know to build your own algorithms that function the way you need them to In Detail Using algorithms in your programming allows you to improve the efficiency, performance, speed, and scalability of your code, applications, and programs. If you're looking to get up and running with algorithms in JavaScript from scratch, then this course is for you. You will learn what algorithms are, why they are important, and how to code them in JavaScript. You will also understand other important programming concepts as you advance such as functional programming, time complexity, and recursion. You'll also discover how to implement them in the algorithms that you build through the course. This course also features useful diagrams and animations to help you learn easily and effectively. The purpose of this course is not to simply help you memorize the algorithms, but instead to guide you on how the code works so you get hands-on experience in working with algorithms. The course covers a mix of ES5 and ES6 code to help you grasp the fundamental concepts easily. By the end of this course, you will have developed the skills you need to make your programs run efficiently using algorithms.